2020
DOI: 10.1177/0145561320907172
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Korean Red Ginseng on Symptoms and Inflammation in Patients With Allergic Rhinitis

Abstract: Korean red ginseng (KRG) has been traditionally used in Korea for health improvement. However, the clinical effect of KRG intake on the symptoms in patients with allergic rhinitis remains unknown. Our study was performed to identify the clinical effects of KRG on patients with allergic rhinitis and to examine the effect of KRG on allergic inflammatory reaction. We evaluated 60 patients with allergic rhinitis. All the patients were treated for 4 weeks. The patients were divided into 3 groups, according to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Moreover, owing to easy access to sinus mucosa, it was possible to administer G-F1 via the intranasal route, where it was therapeutically effective at a much lower dose (3.5 mg/kg) than via intraperitoneal delivery (50 mg/kg), further ensuring favorable efficacy at a safe dose. This dose was also comparable to the dose effective in patients with allergic rhinitis (3 mg/kg/d; the adult dose recommended by the Korea Ginseng Corporation) [ 56 ]. However, a systematic dose range-finding study would be required to establish the therapeutic effect of G-F1 on ECRS in association with NK cells depending upon the route of administration.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, owing to easy access to sinus mucosa, it was possible to administer G-F1 via the intranasal route, where it was therapeutically effective at a much lower dose (3.5 mg/kg) than via intraperitoneal delivery (50 mg/kg), further ensuring favorable efficacy at a safe dose. This dose was also comparable to the dose effective in patients with allergic rhinitis (3 mg/kg/d; the adult dose recommended by the Korea Ginseng Corporation) [ 56 ]. However, a systematic dose range-finding study would be required to establish the therapeutic effect of G-F1 on ECRS in association with NK cells depending upon the route of administration.…”
Section: Discussionmentioning
confidence: 80%
“…These important findings indicated that ginseng supplementation may modulate the resting and post-DH running plasma IL-4 levels in human subjects. In several inflammatory models manipulated by chemicals or diseases, ginseng extract and/or ginsenosides improve severe inflammatory reactions and allergic symptoms by suppressing the levels of pro-inflammatory cytokines [ 66 , 67 ]. IL-4 acts as an anti-inflammatory factor by attenuating the apoptotic activities of neutrophils while promoting the inflammation resolution of macrophages [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the numerous ingredients of KRG, saponins (ginsenosides) are potent candidates that exert anti-inflammatory effects. 24 , 25 , 26 A panaxadiol-type ginsenoside, Rg 3 inhibited expression of inflammatory mediators in mouse skin challenged with the tumor promoter, phorbol ester 27 and LPS/IFN-γ-stimulated BV-2 cells. 28 Another type of ginsenosides, 20( S )-protopanaxatriol, inhibited the expression of COX-2 and iNOS through inactivation of NF-κB in LPS-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%